AKIBAT HUKUM PERJANJIAN JUAL BELI TANAH DENGAN HAK EIGENDOM YANG TIDAK DIKONVERSI (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 756 K/PDT/2019) - Nathania Febriani; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2020)
Legal effect can arise due to legal events that occur from all legal actions, namely actions taken by legal subject towards legal object or any other consequences caused by certain events by the law in question. The agreement in the sale and purchase itself is a legal act that can lead to legal consequences, which seen in the case example by Supreme Court Verdict Number 756 K/PDT/2019. As the case indicated, a cancellation occurred through a decision in court by the judge because there was no proof of conversion of a former eigendom plot of land by the parties. Because any land with western rights that have not been converted since the conversion date has passed will be simultaneously transformed into state land, and the parties only have priority rights to plead their rights to the land. The research method used in this writing is normative legal research method by using both primary legal materials and secondary legal materials. From the results of the study, the cancellation in the sale and purchase agreement was obtained through the role and decision of the judge in the presence of the judge's power in adjudicating a case to uphold justice, if there was no evidence provided that the eigendom land had been converted, then the judge has the authority to cancel the sale and purchase agreement and decide that the party concerned can plead or request his rights to the land itself.